Relations Between Narrative Coherence, Identity, and Psychological Well-Being in Emerging Adulthood - Waters, Theodore E. A.; Fivush, Robyn (Journal of personality, 2015)
The hypothesis that the ability to construct a coherent account of personal experience is reflective, or predictive, of psychological adjustment cuts across numerous domains of psychological science. It has been argued that coherent accounts of identity are especially adaptive. We tested these hypotheses by examining relations between narrative coherence of personally significant autobiographical memories and three psychological well‐being components (i.e., purpose and meaning, positive self‐view, positive relationships). We also examined the potential moderation of the relations between coherence and well‐being by assessing the identity content of each narrative. We collected two autobiographical narratives of personally significant events from 103 undergraduate students and coded them for coherence and identity content. Two additional narratives about generic/recurring events were also collected and coded for coherence. We confirmed the prediction that constructing coherent autobiographical narratives is related to psychological well‐being. Further, we found that this relation was moderated by the narratives' relevance to identity and that this moderation held after controlling for narrative ability more generally (i.e., coherence of generic/recurring events). These data lend strong support to the coherent narrative identity hypothesis and the prediction that unique events are a critical feature of identity construction in emerging adulthood.